Penyuluhan Fisioterapi Low Back Pain pada komunitas Pekerja Industri Roti - Candra Yoga Nanda; Arys Hasta Baruna; Tarmiah (Rena Cipta Mandiri, 2024)
Low Back Pain (LBP) is a common musculoskeletal complaint among industrial workers, especially those performing heavy physical tasks like lifting and maintaining non-ergonomic postures for prolonged periods. This condition can reduce workplace productivity and quality of life. This activity aimed to enhance workers' knowledge and skills in preventing and managing LBP through education and practical training. Ten bread industry workers in Malang City participated in this program, which included lectures on the causes, symptoms, prevention, and management of LBP, as well as stretching exercises to alleviate discomfort. Pre-counseling assessments showed only 10% of participants had knowledge about LBP, but post-counseling evaluations revealed a significant improvement to 100%. These results demonstrate that simple education and exercises can positively impact LBP management. Similar programs are recommended to be implemented regularly to promote workplace health and comprehensively prevent LBP risks.